2015
DOI: 10.1590/s1980-57642015dn91000009
|View full text |Cite
|
Sign up to set email alerts
|

Subjective memory complaints associated with depression and cognitive impairment in the elderly: A systematic review

Abstract: The aging process can be accompanied by a slight decline in cognitive functioning, and subjective memory complaints (SMC) appear to be common in the elderly population.ObjectiveTo determine whether SMC is associated with cognitive loss or depression and can predict dementia.MethodsA systematic review of the literature was conducted. Articles were selected on the following databases, LILACS, SCOPUS, SCiELO, PubMed and Web of Science from August to October 2013. Article selection was based on inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 30 publications
5
34
1
6
Order By: Relevance
“…Unlike other studies (Brigola et al, 2015;Silva et al, 2014), the present study showed no relationship between depression and cognitive state, which is in agreement with the results reported by Paulo and Yassuda (2010).…”
Section: Discussionsupporting
confidence: 93%
“…Unlike other studies (Brigola et al, 2015;Silva et al, 2014), the present study showed no relationship between depression and cognitive state, which is in agreement with the results reported by Paulo and Yassuda (2010).…”
Section: Discussionsupporting
confidence: 93%
“…Memory loss is a major problem in older adults [27,28], including AA older adults [27,[29][30][31]. Memory loss, which is different from dementia [32], reduces the quality of life [28], impairs disease management [33], predicts mortality [34], and predicts a wide range of undesirable health outcomes [28,35]. Memory loss is also a source of economic burden to families, health care systems, and society [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the association between depressive symptoms and SMCs has been one of the most robust findings in scientific research (Brigola et al, 2015;Lehrner et al, 2014;Montejo Carrasco et al, 2017;Sousa et al, 2015;Zlatar, Muniz, Galasko, & Salmon, 2017). However, the neural correlates of the comorbidity between depressive symptoms and SMCs have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals with SMCs as early as in middle-age have shown significant cortical thinning in several brain regions that are commonly affected in AD, including the entorhinal, posterior cingulate, and inferior parietal cortices, compared with healthy control subjects (Schultz et al, 2015). However, most previous studies related to SMCs and depression have primarily focused on the elderly (Brigola et al, 2015;Montejo Carrasco et al, 2017). Given that SMCs can arise as early as middle-age, along with the fact that management of early risk factors may mitigate further cognitive impairment (Byers & Yaffe, 2011;Hughes & Ganguli, 2009), it would be more informative and beneficial to investigate the neural mechanisms of depressive symptoms in middleaged individuals with SMCs rather than in the elderly.…”
Section: Introductionmentioning
confidence: 99%